Study on mass concentration and morphology of SMAW fume particles with a new covered electrode using nano-CaTiO3 as an arc stabilizer. (December 2022) - Rahul, M.; Sivapirakasam, S.P.; Mohan, Sreejith; Vishnu, B.R.; Gomes, J.F.P.
Abstract: Advances in manufacturing emphasize on the development of sustainable and green manufacturing processes. Welding is a popular manufacturing process practiced worldwide. The paper presented here describes a new covered electrode for a shielded metal arc welding (SMAW) process wherein nano-sized calcium titanate (CaTiO3 ) powder was used as an arc stabilizer, replacing the conventional micro sized CaTiO3 in the flux. The effect of this flux modification on the mass concentration and morphology of welding fume particulates was systematically investigated. The mass concentration of coarse, fine and sub-micron sized fume particulates was measured by segregating the fumes in a four-stage personal cascade impactor. The particle mass distribution was estimated from the mass median aerodynamic diameter (MMAD) and geometric standard deviation (GSD) of the fume particulates. The morphology of fumes at each impactor stage was analysed using scanning electron microscopy and its count median diameter (CMD) was determined. The results indicated as much as 48 % reduction in total fumes and 54 % reduction in the breathing zone concentration of fumes when the entire CaTiO3 in the electrode flux was substituted with nano-CaTiO3 . Morphological analysis indicated that a large fraction of the fumes from the conventional electrode were polydispersed particles, while the new electrodes predominantly contained monodispersed particles which have a relatively faster rate of removal from the lungs. Overall, the present work indicated that introducing nano sized CaTiO3 as an arc stabilizer to the flux covering of SMAW electrode could not only reduce the hazardous fume emissions but also reduce its biological activity and toxicity, thus making the process more sustainable and environment friendly.